Flagellar motility is necessary for Aeromonas hydrophila adhesion. (September 2016) - Qin, Yingxue; Lin, Guifang; Chen, Wenbo; Xu, Xiaojin; Yan, Qingpi
Abstract: Adhesion to host surface or cells is the initial step in bacterial pathogenesis, and the adhesion mechanisms of the fish pathogenic bacteria Aeromonas hydrophila were investigated in this study. First, a mutagenesis library of A. hydrophila that contained 332 random insertion mutants was constructed via mini-Tn10 Km mutagenesis. Four mutants displayed the most attenuated adhesion. Sequence analysis revealed that the mini-Tn10 insertion sites in the four mutant strains were flgC (GenBank accession numbers KX261880), cytb4 (GenBank accession numbersJN133621 ), rbsR (GenBank accession numbers KX261881) and flgE (GenBank accession numbersJQ974982 ). To further study the roles of flgC and flgE in the adhesion of A. hydrophila, some biological characteristics of the wild-type strain B11, the mutants M121 and M240, and the complemented strains C121 and C240 were investigated. The results showed that the mutation in flgC or flgE led to the flagellar motility of A. hydrophila significant reduction or abolishment. flgC was not necessary for flagellar biosynthesis but was necessary for the full motility of A. hydrophila, flgE was involved in both flagellar biosynthesis and motility. The flagellar motility is necessary for A. hydrophila to adhere to the host mucus, which suggests flagellar motility plays crucial roles in the early infection process of this bacterium. Highlights: The flagellar motility is necessary for Aeromonas hydrophila to adhere to the host mucus. flgC was not necessary for flagellar biosynthesis but was necessary for the full motility of A. hydrophila . flgE was involved in both flagellar biosynthesis and motility.